The Effects of Alignment of Educational Expectations and Occupational Aspirations on Labor Market Outcomes: Evidence from NLSY79. (2nd November 2019) - Kim, Soobin; Klager, Christopher; Schneider, Barbara
ABSTRACT: Using data from the National Longitudinal Survey of Youth of 1979, this article examines the relationship between adolescents' educational and occupational expectations, and how they correspond to their subsequent labor market outcomes in adulthood. We show that over-aligned adolescents, those who expect to obtain more education than is necessary for their desired occupation, are predicted to have hourly wages 30% higher than under-aligned adolescents, whose educational expectations are lower than their occupational expectations. The misalignment of educational and occupational expectations is not related to the probability of being employed through individuals' early twenties to late forties. However, over-aligned individuals are predicted to have more prestigious occupations than under-aligned individuals, suggesting that those in the over-aligned group sorted into better jobs over their careers. We also show that the effects of misaligned expectations on labor market outcomes change over the years, indicating that having high and aligned expectations are even more important for labor market outcomes than previously estimated.